Potential of nanocellulose as a dietary fiber isolated from brewer’s spent grain - Morales Juárez, Abraham Azael; Terrazas Armendáriz, Luis Daniel; Alcocer González, Juan Manuel; Chávez Guerrero, Leonardo (Molecular Diversity Preservation International, 2023)
Steady growth in beer production is increasing the number of by-products named brewers’ spent grain. Such by-products are a source of several components, where cellulose is usually present in high amounts. The aim of this study was to develop a protocol to obtain a mix of cellulose microfibers with an average diameter of 8–12 µm and cellulose nanoplatelets with an average thickness of 100 nm, which has several applications in the food industry. The process comprised one alkaline treatment followed by acid hydrolysis, giving a new mix of micro and nanocellulose. This mix was characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, and laser scanning microscopy corroborating the presence and measurements of the cellulose nanostructure, showing an aspect ratio of up to 500. Finally, we demonstrated that the administration of this new type of nanocellulose allowed us to control the weight of mice (feed intake), showing a significant percentage of weight reduction (4.96%) after 15 days compared with their initial weight, indicating the possibility of using this material as a dietary fiber